1983
DOI: 10.1002/pssb.2221190219
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the charge carrier concentration and mobility in n‐gap by Raman spectroscopy

Abstract: A method is presented which allows the determination of the charge carrier concentration and mobility in n-GaP by Rainan spectroscopy of coupled plasmon-phonon modes. The results a m compared with those of electrical measurements.Es wird eine Methode fur die Bestimmung der Konzentration freier Ladungstrager und deren Beweglichkeit in n-GaP mittels Raman-spektroskopischer Messungen gekoppelter Plmmon-PhononModen vorgestellt. Die Ergebnisse werden mit denen elektrischer Messungen verglichen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
4

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(85 citation statements)
references
References 8 publications
8
73
0
4
Order By: Relevance
“…Nevertheless, the plasmon-phonon coupling of GaP is much less explored than GaAs. Previous Raman studies [37][38][39][40] reported that, as in GaAs, the LOPC frequency upshifted from ν LO upon n-type doping, though the lower branch was never observed. Upon p-type doping, the LOPC frequency of GaP upshifted slightly from ν LO 39,40 , contrary to the downshift that is established for p-type GaAs.…”
Section: Introductionmentioning
confidence: 88%
“…Nevertheless, the plasmon-phonon coupling of GaP is much less explored than GaAs. Previous Raman studies [37][38][39][40] reported that, as in GaAs, the LOPC frequency upshifted from ν LO upon n-type doping, though the lower branch was never observed. Upon p-type doping, the LOPC frequency of GaP upshifted slightly from ν LO 39,40 , contrary to the downshift that is established for p-type GaAs.…”
Section: Introductionmentioning
confidence: 88%
“…Many of the LOPCM analyses of Raman spectra in polar semiconductors have been carried out using either a Drude model 12,34,35 or the hydrodynamical model 4,10,36,37 for the free-carrier electric susceptibility. The computational simplicity of these two models as compared with the more involved Lindhard-Mermin calculations has favored their widespread use in the analysis of Raman spectra.…”
Section: Comparison Between the Drude And The Hydrodynamical Modelmentioning
confidence: 99%
“…The values of the reduced Fermi energy (E F /k B T) found for samples A -H range from Ϫ1. 35 for the lowest doping sample ͑A͒, to 8.27 for the highest doping sample ͑H͒. Consequently, the use of the Fermi-Dirac distribution function is necessary for a realistic description of the electron plasma through the whole range of carrier concentrations.…”
mentioning
confidence: 99%
“…In n-type samples, the predominant mechanism causing the Raman shift of the LO mode is the coupling interaction between LO phonons and overdamped plasmons [35,36].…”
Section: Raman Spectroscopymentioning
confidence: 99%